Pengenalan Pola Hidup Bersih dan Sehat Melalui Exprimen Sains pada Anak Usia Dini di Kelompok B TK Putri Ramadhani - Novita Ashari; Putri Indah Sari; Armi Nadilah Asnar; Harianti Harianti; Megawati Megawati; Mogawani Mogawani; Ema Ainun Kholilah; Lisma Widyarni (The Center for Gender and Children Studies, the Institute for Research and Communing Service, State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2021)
The lack of knowledge and understanding of children in Putri Ramadhani Kindergarten about Clean and Healthy Living Behavior (PHBS) is because children have not been motivated to maintain a clean and healthy lifestyle, children have not carried out direct experiments on maintaining cleanliness. Children are only introduced through visual images. The purpose of this study was to provide understanding to children about a Clean and Healthy Lifestyle through scientific experiments. The implementation of the introduction of a healthy and clean lifestyle that has been carried out at the Putri Ramadhani Kindergarten has been carried out well by the children, this is shown in the increase in the cleanliness of children aged 4-5 in the Putri Ramadhani Kindergarten which amounted to 10 children. Of the 4 indicators of clean and healthy living that children are accustomed to, namely washing hands before eating without being asked, knowing the order of washing hands, closing their own lunch after eating without being asked, knowing the dangers of germs, viruses, and bacteria. Abstrak Kurangnya pengetahuan dan pemahaman anak di TK Putri Ramadhani tentang Perilaku Hidup Bersih dan Sehat (PHBS) hal tersebut dikarenakan anak belum termotivasi untuk menjaga pola hidup bersih dan sehat anak belum melakukan eksprimen langsung tentang menjaga kebersihan. Anak hanya di kenalkan melalui visual gambar saja. Tujuan penelitian ini adalah untuk memberikan pemahaman kepada anak Pola Hidup Bersih dan Sehat melalui ekperimen sains. Pelaksanaan pengenalan pola hidup sehat dan bersih yang telah dilakukan pada TK Putri Ramadhani telah terlaksanakan dengan baik oleh anak, hal ini ditunjukkan pada kebersihan anak usia 4-5 di TK Putri Ramadhani yang berjumlah 10 anak meningkat. Dari 4 indikator hidup bersih dan sehat yang dibiasakan anak yaitu mencuci tangan sebelum makan tanpa disuruh, mengetahui urutan mencuci tangan, menutup bekal sendiri setelah makan tanpa disuruh, mengetahui bahaya kuman, virus, dan bakteri.